Association of exposure to PM2.5 and PM10 with DNA damage in exfoliated buccal mucosa cells among primary school children living nearby palm oil activity at Semenyih, Selangor - Othman, Syhidatul Farhana; Jalaludin, Juliana; Hisamuddin, Nur Hazirah; Widajati, Noeroel (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2019)
Introduction: Exposure of PM2.5 and PM10 released from combustion of biomass activity caused respiratory health among children. Objective: This study aims to determine the association between exposure of PM2.5 and PM10 with DNA damage in primary school children living nearby palm oil combustion activity at Semenyih. Methods: A cross sectional comparative study were conducted among Malay primary school children in school A located 2.7km from palm oil activity (N=82) and school B located about 40km away from the palm oil area (N=85). A standardized questionnaire were distributed to respondent’s parents. Concentrations of PM2.5 and PM10 were measured by using Dust Trak DRX Aerosol Monitor Model 8534 and Escort LC Personal Sampling Pump. Measurement of indoor and outdoor air pollutants were conducted in schools and home. Buccal cells were collected, which then followed by micronucleus assay. Results: Concentration of PM10 and PM2.5 at home of studied group were significantly higher compared to comparative group with p value (p=0.007) and (p=0.018) respectively. PM10 and PM2.5 of studied schools were significantly higher compared to comparative schools with p value (p=0.014) and (p=0.04) respectively. MN frequencies of studied group were significantly higher compared to comparative group (p=0.001). Significant difference of respiratory symptoms were found between two groups which are cough, phlegm, wheezing and chest tightness (p=0.001). There were significant correlation between PM10 with MN frequency of studied group and comparative group with r= 0.562; p=0.001. Conclusion: This study indicated that the exposure of PM10 and PM2.5 would increase the risk of having respiratory health symptoms and might induce the micronuclei formation among children who lived near palm oil activity area.